Dinamika Komunikasi Awal Perempuan Pengguna Bumble: Strategi dan Faktor Keberhasilan - Chrysantia, Adelya; Junaidi, Ahmad (Kiwari, 2026)
This study analyzes the success of women's initial interactions on the Bumble dating app amid advancements in information and communication technology that are transforming digital interpersonal communication, particularly through the unique "women first move" feature, which empowers women as conversation initiators. This phenomenon is relevant in Indonesia, where the rapid growth of dating app users among urban youth means the initial stage determines relationship continuation through factors such as shared interests, communication activity, and a sense of security. The research aims to analyze women's initial communication strategies on Bumble and identify success determinants, including activity, consistency, comfort, and barriers. Employing a descriptive qualitative approach, with in-depth interviews of active female users, male supporters, and communication experts, the data were analyzed through source triangulation and member checking to ensure validity. Findings reveal strategies dominated by authentic self-presentation via natural profiles, simple opening messages, consistent communication rhythms; the control feature enhances security and selectivity; success is influenced by two-way communication activity, shared interests, balanced comfort, while barriers like symbol misinterpretation are adaptively overcome, contributing to gender- sensitive digital communication in Indonesia. Penelitian ini menganalisis keberhasilan interaksi awal perempuan di aplikasi kencan Bumble di tengah perkembangan teknologi informasi dan komunikasi yang mengubah pola komunikasi interpersonal digital, khususnya melalui fitur unik "women first move" yang memberdayakan perempuan sebagai inisiator percakapan. Fenomena ini relevan di Indonesia dengan pertumbuhan pengguna dating apps di kalangan generasi muda urban, di mana tahap awal menentukan kelanjutan hubungan melalui faktor kesamaan minat, keaktifan komunikasi, dan rasa aman. Tujuan penelitian adalah menganalisis pola strategi komunikasi awal perempuan di Bumble serta mengidentifikasi faktor penentu keberhasilan seperti keaktifan, konsistensi, kenyamanan, dan hambatan. Menggunakan pendekatan kualitatif deskriptif dengan wawancara mendalam terhadap informan perempuan pengguna aktif, laki-laki pendukung, dan ahli komunikasi, data dianalisis melalui triangulasi sumber dan member check untuk validitas. Hasil menunjukkan strategi didominasi pengelolaan citra autentik melalui profil natural, pesan pembuka sederhana, ritme komunikasi konsisten; fitur kontrol meningkatkan rasa aman dan selektivitas; keberhasilan dipengaruhi keaktifan komunikasi dua arah, kesamaan minat, kenyamanan seimbang, sementara hambatan misinterpretasi simbol diatasi adaptif, berkontribusi pada komunikasi digital gender-sensitive di Indonesia.